Complete mitogenome of the Oven's halosaur, Halosaurus ovenii (Elopomorpha; Notacanthiformes). Issue 4 (3rd April 2021) - Barros-García, David; Gomes-dos-Santos, André; Machado, André M.; Castro, L. Filipe C.; de Carlos, Alejandro; Bañón, Rafael; Bruno, Isabel; Arronte, Juan C.; Froufe, Elsa
Abstract: The difficulties involved in the study of deep-sea species imply the existence of a wide gap in knowledge of this ecosystem. Here, we have obtained the mitogenome of the Oven's halosaur, Halosaurus ovenii, for the first time using low coverage Illumina Paired-end (PE) sequencing. This species belongs to order Notacanthiformes, a poorly studied group of deep-sea fishes. Moreover, given their evolutionary placement, they are critical to investigate the early diversification of the Teleostei. The assembled mitogenome displays the expected gene arrangement for vertebrate mtDNA. Phylogenetic analyses combining all the available mitogenomes of the Order Notacanthiformes were performed. The evolutionary relationships among H. ovenii and the rest of the Halosauridae family were confirmed. This mitogenome provides a valuable baseline for future research of H. ovenii .